LITERATURE ON TERRORISM: A BIBLIOMETRIC ANALYSIS OF ARTICLES PUBLISHED DURING 1981-1990 - Mumtaz, A. Anwar; Sultan, Al-Daihani (Malaysian Journal of Library and Information Science, 2017)
This study conducted a bibliometric analysis of papers on terrorism published in journals from 1981- 1990. The 402 citations were retrieved from Social Science Citation Index (SSCI) via DIALOG. Thefindings show that the annual growth of this literature is unstable. These papers come from many disciplines indicating that terrorism has not yet developed into a specialty. The literature is dispersed, mostly thin, in 139 journals with no identifiable core. Single-author and English language publications are dominant. Most of the papers originate in the U.S.A and U.K. It is suggested that indexing should be expanded to cover journals published in developing countries and their languages. It is also suggested that studies on larger samples should be conducted to identify rates of growth, core authors, core journals, and changes in research topics.